Comparison of the collection of blood samples in prenatal screening, using the filter paper and venipuncture technique ELISA for the detection of HIV 1+2 - Gómez, Juan Fidel Bencomo; Appolinário, Marco A.O.; Abreu, Dolores M.F.; Castro, Antonio J.W.; Martí, Jordi; Prates, Sidney; Santos, Cristimar dos (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: although the filter paper (FP) have been introduced since the last century (1963) by Guthrie and Susi, in neonatal screening as an alternative to blood sample collection, its benefits in the application of medical laboratory practice not were used effectively in recent years, with the exception of the recent results obtained in the works for the prenatal screening. Early diagnosis of HIV in pregnant women is of paramount importance, being the most outstanding support to counteract the vertical transmission (VT) of HIV-AIDS, because the determination of the presence of HIV antibodies, it applies to the ACTG 076 Protocol (Pediatric AIDS Clinical Trials Group Study Group), which is the treatment of pregnant HIV-positive in the pre-, intra and post-parto. Objetive: compare the collection of blood samples on filter paper (FP) and plasma (standard gold) in prenatal screening, using antibodies against HIV 1 +2 ELISA immunochemical procedure (Imunoscreen HIV 1 +2 SS), the firm Mbiolog. Methods: we studied 1,142 pregnant women in four counties of the State of Rio de Janeiro: Itaboraí (N = 131), Itaguaí (N = 597), Niterói (N = 377) and St. John Meriti (N = 37), from November 2008 until February 2009. The pregnant women underwent fingerstick and venous for routine prenatal screening, the first being applied in PF. We calculated the limits of sensitivity, specificity and positive predictive value and negative for the study. Results: the results of absorbance (homogeneity of variances) for the samples found non-reactive and reactive in both techniques, showed no significant differences (P > 0.05) when using the Student’s T test in the study of repeatability. Reproducibility studies for both techniques did not result in coefficients of variation above 10%. Conclusion: the results of serological tests for HIV in dried blood collected in PF were similar to the collection by venipuncture, validating this technique.